Stem/progenitor cells in the developing human lung - Daniela Fanni; Margherita Fanos; Clara Gerosa; Flaviana Cau; Erika Pisu; Peter Van Eyken; Rossano Ambu (Hygeia Press di Corridori Marinella, 2016)
Human lungs are composed of more than 40 cell types. The lung is classified as a "conditionally renewing" tissue and is able of a quick response to cellular damage thanks to the presence of multiple stem/progenitor cells. Embryonic and fetal progenitors actively proliferate determining lung size, shape and cellular composition and could be of paramount importance in understanding lung development and mechanisms of congenital diseases. Furthermore, developmental molecular pathways may be chronically or aberrantly activated in tumorigenesis or in lung diseases later in life. Lungs have a mixed endodermal and mesodermal origin. Endoderm progenitors are early marked by TTF1. Other reported markers of endodermal respiratory progenitors are Sox2, Sox9 and Id2. Proximal versus distal differentiation is guided by the expression of Fgf10. Little is known about mesodermal stem/progenitor cells in the developing lung. A signaling interplay among endoderm, mesoderm and mesothelium plays a role in the signaling network. Our preliminary data stress the importance of the interaction of the endodermal component, giving rise to tubular structures, and the mesodermal component, that showed the tendency to acquire a concentric onion-like or solid or nests arrangement. Subpleural niches appeared in strict contact with the thin pleural mesothelium and were formed by a complex array of cell types. At immunohistochemistry, nuclear reactivity for TTF1 was found in the interior layer of the epithelial tips, while the endodermal component of the developing lung showed positivity for SOX-2, and CD34 revealed the newly formed vascular structures inside the lung mesenchyme. In conclusion, the complexity of the histological picture of the developing human lung is emphasized by the multiple stem/progenitor cells. The endodermal and mesodermal ones, through complex processes of differentiation, act together in order to give rise to a huge number of cell types.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano